Evaluating preference for and reinforcing efficacy of fruits and vegetables compared with salty and sweet foods. Issue 1 (20th June 2019) - Kronfli, Faris R.; Vollmer, Timothy R.; Fernand, Jonathan K.; Bolívar, Hypatia A.
Abstract : Children diagnosed with autism spectrum disorder are often more selective in their food preferences than their typically developing peers. Additionally, many preferred food selections have minimal nutritional value. We evaluated the preference for, and reinforcing efficacy of, fruits and vegetables compared with salty and sweet foods, which are often used as edible reinforcers. Multiple‐stimulus preference assessments were conducted to identify preferred foods, and reinforcer assessments were conducted to determine the reinforcing efficacy of more preferred foods. Fruits and vegetables were sometimes preferred over salty or sweet foods and often functioned as reinforcers. Future research should incorporate fruits and vegetables into preference assessments when identifying putative reinforcers.